2016
DOI: 10.1007/s00204-016-1877-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of the lipid-regulated NF-κB/IL-6/STAT3 axis in alpha-naphthyl isothiocyanate-induced liver injury

Abstract: Alpha-naphthyl isothiocyanate (ANIT)-induced liver damage is regarded as a useful model to study drug-induced cholestatic hepatitis. Ultra-performance liquid chromatography coupled with electrospray ionization quadrupole mass spectrometry (UPLC-ESI-QTOF MS)-based metabolomics revealed clues to the mechanism of ANIT-induced liver injury, which facilitates the elucidation of drug-induced liver toxicity. 1-Stearoyl-2-hydroxy-sn-glycero-3-phosphocholine (LPC 18:0) and 1-oleoyl-2-hydroxy-sn-glycero-3-phosphocholine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…ANIT is a hepatotoxicant used in mice and rats to model human drug-induced intrahepatic cholestasis. One recent study found that two LPCs were increased in serum of ANIT-induced mice cholestasis and demonstrated the role of lipid-regulated NF-κB/IL-6/STAT3 axis in ANIT-induced liver injury 18 . In the present study, using metabolomics revealed that a series of long-chain acylcarnitines were increased in the serum of ANIT-induced cholestasis model indicated the impaired β -FAO.…”
Section: Discussionmentioning
confidence: 99%
“…ANIT is a hepatotoxicant used in mice and rats to model human drug-induced intrahepatic cholestasis. One recent study found that two LPCs were increased in serum of ANIT-induced mice cholestasis and demonstrated the role of lipid-regulated NF-κB/IL-6/STAT3 axis in ANIT-induced liver injury 18 . In the present study, using metabolomics revealed that a series of long-chain acylcarnitines were increased in the serum of ANIT-induced cholestasis model indicated the impaired β -FAO.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of combination therapy with UDCA remains to be investigated. The ANIT‐induced model of cholestasis was mainly used in this study, because it is a widely accepted cholestasis model and the pathological changes are very similar to those of human intrahepatic cholestatic liver disease (Goldfarb et al , ; Fang et al , ; Liu et al , ). DDC was used as an animal model to study chronic PSC (Liedtke et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Experiment 1: To find the common increased ions in ANIT-and TAA-induced cholestasis, WT mice were randomly assigned into four groups (n ϭ 6): (1) ANIT-Control; (2) ANIT; (3) TAA-Control; (4) TAA. ANIT group was given a single oral dose of ANIT (75 mg/kg dissolved in corn oil) (15), and TAA group was given a single intraperitoneal dose of TAA (300 mg/kg dissolved in physiologic saline solution) (16). Experiment 2: To investigate the protective effect of celastrol on ANIT-induced cholestasis, the WT (n ϭ 6) and Fxr-null (n ϭ 5) mice were randomly assigned into three groups, respectively: (1) control; (2) ANIT; (3) ANITϩCelastrol.…”
Section: Methodsmentioning
confidence: 99%